2002
DOI: 10.1507/endocrj.49.589
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Telomerase Activity in Experimentally Induced Atretic Follicles of Immature Rats.

Abstract: Follicular atresia is characterized by apoptosis of granulosa cells, and telomerase plays an important role in the apoptotic process. To study the relationship between follicular atresia and telomerase activity, we investigated changes in telomerase activity and localization in experimentally induced atretic follicles of immature rats. Immature female Sprague-Dawley rats received 15 IU equine CG (eCG) by subcutaneous injection. Rats were killed under ether anesthesia at 2, 3, 4, or 5 days after eCG injection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 24 publications
4
45
0
Order By: Relevance
“…Similar results were obtained by Yamagata et al (2002), who observed a higher level of telomerase activity in healthy, preovulatory follicles as a result of estradiol application to female rats. Estradiol produced by growing follicles is an antiatretic factor, increasing the survivability of the follicular cells.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similar results were obtained by Yamagata et al (2002), who observed a higher level of telomerase activity in healthy, preovulatory follicles as a result of estradiol application to female rats. Estradiol produced by growing follicles is an antiatretic factor, increasing the survivability of the follicular cells.…”
Section: Discussionsupporting
confidence: 88%
“…Telomerase activity was also detected in the human endometrium, and its level correlated with estrogen changes, being the highest in the follicular phase of the estrus cycle (Kyo et al, 1997;Yokoyama et al, 1998). Application of estradiol to female rats prevented decrease of telomerase activity in granulosa cells (Yamagata et al, 2002). The role of estrogens in telomerase activity regulation in pig granulosa cells is not fully understood.…”
mentioning
confidence: 99%
“…Interestingly, it was shown that there is no significant difference between pig small antral and large antral follicles in telomerase activity of granulosa cells [74]. Additionally, a significantly decreased telomerase activity was observed in large and atretic follicles in comparison to small and healthy follicles in rat [83]. In human the low level of telomerase activity in the ovary was found to be related to the age-related primordial follicle depletion and it was speculated that telomerase activity could be used as a marker of the ovarian functional age [35].…”
Section: Telomerase Activity and Stemness In Granulosa Cellsmentioning
confidence: 96%
“…In the present study we focused on the expression of genes for two subtypes of oestrogen receptor in pig granulosa cells cultured in the presence of LIF, bFGF, or SCF. The rationale behind undertaking this study is the well-established role of oestrogens in maintaining granulosa cell survivability (Yamagata et al, 2002). Therefore, it was interesting to elucidate if and how the level of oestrogen receptors is changed under the influence of different growth factors during prolonged culture of GC obtained from follicles of different sizes.…”
Section: Discussionmentioning
confidence: 99%
“…Its production in atretic follicles is significantly decreased. Yamagata et al (2002) found a decreased level of telomerase activity in experimentally induced atretic rat follicles. Administration of oestradiol to female rats prevented both follicular atresia as well as a decrease of telomerase activity in granulosa cells.…”
Section: Introductionmentioning
confidence: 90%